Realtime power quality evaluation system of the electric propulsion ship based on AHP-fuzzy comprehensive evaluation method - Zhang Wenbao; Shi Weifeng; Lan Ying; Gu Siyu; Zhuo Jinbao (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] With the wide application of power electronic devices in electric propulsion ships and the increasing capacity of marine electric power systems,the problem of ship power quality has become increasingly prominent. In view of the issues above,a realtime power quality evaluation system is designed.[Methods] Firstly,the advantages,disadvantages and feasibility of the mainstream power quality assessment algorithms were analyzed based on the characteristics of the electric power system the ships and the research status of the ship power quality. Then,according to the latest evaluation criteria,a multi-level evaluation system containing eight power quality indexes which can reflect the operating characteristics of marine electric power system was constructed and the ship's power quality realtime evaluation system based on the Analytic Hierarchy Process(AHP)-Fuzzy Comprehensive Evaluation (FCE) method was proposed. Finally, the feasibility test based on the electric propulsion ship experimental device was carried out and the corresponding Graphic User Interface(GUI)was designed by Matlab software.[Results] The evaluation system can realize the realtime evaluation and scoring of the ship's power quality at 1 s level and generate qualitative and quantitative results at the same time.[Conclusions] AHP-FCE method can be successfully applied to the realtime evaluation system of ship power quality,which is conducive to improving the centralized monitoring and management of marine electric power system equipment and provides a new design idea for the application of other evaluation methods in marine fields.